HUSNUZAN AND QUARTER-LIFE CRISIS IN STUDENTS OF RADEN MAS SAID ISLAMIC STATE UNIVERSITY SURAKARTA - Pratiwi, Putri Anaida; Saifuddin, Ahmad (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2024)
Adolescence is a crucial stage in the human developmental phase because adolescents typically experience various problems. One of the problems is the quarter-life crisis (QLC). QLC is a problem related to anxiety about multiple roles that have yet to be completed in the adolescence phase, such as university, work, and marriage. Literature mentions that QLC can be buffered by husnuzan. However, the authors found that some Raden Mas Said Islamic State University Surakarta (Universitas Islam Negeri Raden Mas Said Surakarta) students who are in adolescence and implementing husnuzan still experience QLC. Thus, the present study aimed to explain the correlation between husnuzan and a quarter-life crisis. The study used a correlational quantitative approach. Therefore, data collection instruments were in the form of Likert scales. Six experts validated the husnuzan and QLC instruments to ensure their validity. The two instruments were also tested, resulting in a reliability coefficient of 0.941 for the QLC scale and 0.908 for the husnuzan scale. The study involved 300 UIN Raden Mas Said Surakarta students aged 21-25 years old. An analysis with regression analysis showed F=178.523 and β=-0.612 with p<0.01. In other words, there is an effect of husnuzan on quarter-life crisis among students of UIN Raden Mas Said Surakarta. In the context of da'wah, this research is expected to be a reference theme for preachers targeting adolescents and preachers' efforts to overcome the problems of adolescents.